Correlation of selenium and zinc levels to antiretroviral treatment outcomes in Thai HIV-infected children without severe HIV symptoms - T. Bunupuradah (2018)
Background/Objectives:Deficiencies in antioxidants contribute to immune dysregulation and viral replication. To evaluate the correlation of selenium (Se) and zinc (Zn) levels on the treatment outcomes in HIV-infected children.Subjects/Methods:HIV-infected Thai children 1-12 years old, CD4 15-24%, without severe HIV symptoms were included. Se and Zn levels were measured by graphite furnace atomic absorption spectrometry at baseline and 48 weeks. Deficiency cutoffs were Se 0.1 mol/l and Zn 9.9 mol/l. Serum ferritin and C-reactive protein (CRP) were measured every 24 weeks. No micronutrient supplement was prescribed.Results:In all, 141 children (38.3% male) with a median (interquartile range (IQR)) age of 7.3 (4.2-9.0) years were enrolled. Median baseline CD4% was 20%, HIV-RNA was 4.6 log 10 copies/ml. At baseline, median (IQR) Se and Zn levels were 0.9 (0.7-1.0) mol/l and 5.9 (4.8-6.9) mol/l, respectively. None had Se deficiency while all had Zn deficiency. Over 48 weeks, 97 initiated antiretroviral therapy (ART) and 81% achieved HIV-RNA 50 copies/ml with 11% median CD4 gain. The mean change of Se was 0.06 mol/l (P0.003) and Zn was 0.42 mol/l (P0.003), respectively. By multivariate analysis in children who received ART, predictors for greater increase of CD4% from baseline were lower baseline CD4% (P0.01) and higher baseline Zn level (P0.02). The predictors for greater decrease of HIV-RNA from baseline were higher baseline HIV-RNA and higher ferritin (both P0.01). No association of CRP with the changes from baseline of CD4% or HIV-RNA was found.Conclusion:In HIV-infected Thai children without severe immune deficiency who commenced ART, no correlation between Se and ART treatment outcomes was found. Higher pre-ART Zn levels were associated with significant increases in CD4% at 48 weeks. © 2012 Macmillan Publishers Limited.